Gamma Low-Dose-Rate Ionizing Radiation Stimulates Adaptive Functional and Molecular Response in Human Aortic Endothelial Cells in a Threshold-, Dose-, and Dose Rate–Dependent Manner. Issue 1 (2nd March 2018) - Vieira Dias, Juliana; Gloaguen, Celine; Kereselidze, Dimitri; Manens, Line; Tack, Karine; Ebrahimian, Teni G
A central question in radiation protection research is whether low-dose and low-dose-rate (LDR) exposures to ionizing radiation play a role in progression of cardiovascular disease. The response of endothelial cells to different LDR exposures may help estimate risk of cardiovascular disease by providing the biological mechanism involved. We investigated the effect of chronic LDR radiation on functional and molecular responses of human aorta endothelial cells (HAoECs). Human aorta endothelial cells were continuously irradiated at LDR (6 mGy/h) for 15 days and analyzed at time points when the cumulative dose reached 0.05, 0.5, 1.0, and 2.0 Gy. The same doses were administered acutely at high-dose rate (HDR; 1 Gy/min). The threshold for the loss of angiogenic capacity for both LDR and HDR radiations was between 0.5 and 1.0 Gy. At 2.0 Gy, angiogenic capacity returned to normal only for HAoEC exposed to LDR radiation, associated with increased expression of antioxidant and anti-inflammatory genes. Pre-LDR, but not pre-HDR, radiation, followed by a single acute 2.0 Gy challenge dose sustained the expression of antioxidant and anti-inflammatory genes and stimulated angiogenesis. Our results suggest that dose rate is important in cellular response and that a radioadaptive response is involved for a 2.0 Gy dose at LDR.